2009
DOI: 10.1007/s11205-009-9536-4
|View full text |Cite
|
Sign up to set email alerts
|

Independent Correlates of Reported Gambling Problems Amongst Indigenous Australians

Abstract: Aboriginal populations, Public health policy, Gambling,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
(28 reference statements)
2
19
0
Order By: Relevance
“…Official review bodies reached the same conclusion (Gambling Review Body 2001;National Research Council 1999;Productivity Commission 1999). Associations between participation and gambling problems have been shown to be particularly strong in the case of activities that are continuous and involve an element of skill or perceived skill such as EGMs, casino table games and sports betting (Abbott 2007;Binde 2011;Stevens and Young 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Official review bodies reached the same conclusion (Gambling Review Body 2001;National Research Council 1999;Productivity Commission 1999). Associations between participation and gambling problems have been shown to be particularly strong in the case of activities that are continuous and involve an element of skill or perceived skill such as EGMs, casino table games and sports betting (Abbott 2007;Binde 2011;Stevens and Young 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The multivariable model for carer reported gambling problems contained community access to doctor, carer cohabitation with spouse unknown, three or more young children in the house (a measure of crowding), and poor carer psychosocial health. These associations reinforce that gambling, as an activity, does not occur in isolation of the social and physical aspects of the community, which can influence both propensity for people to gamble and consequences (harmful or not) resulting from excessive gambling [3,5,10,11,34]. An analysis of the National Aboriginal and Torres Strait Islander Social Survey at both the national and NT level also found that community level variables, namely having gang, family violence, alcohol and physical assault problems in the community showed evidence for a multivariate adjusted association with increased reporting of gambling problems [10,11].…”
Section: Discussionmentioning
confidence: 85%
“…Respondents are asked if ‘gambling problems’ have been a problem for themselves, a family member or a close friend in the last year. Across Australia in 2002, 26% of Indigenous people in remote localities reported gambling problems, while the same figure was 10% for the non-remote Indigenous population, compared with 3.5% within the general population [10,11]. In the NT, the same figures for remote Indigenous, non-remote Indigenous and the general population were 32%, 11% and 3% respectively [12].…”
Section: Introductionmentioning
confidence: 99%
“…Dion et al (2010) suggested that prior studies on Aboriginal gambling cannot be generalized to the entire population, and that exceptionally high prevalence rates may only reflect local conditions in some specific communities. For example, Aboriginal people living in remote regions of Australia had higher rates of gambling problems than those living in urban regions (Stevens and Young 2010). The authors suggested that crowding in multi-family homes, low income levels, attendance at sports events and carnivals, and involvement in indigenous organizations were related to variations in gambling rates (Stevens and Young 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Aboriginal people living in remote regions of Australia had higher rates of gambling problems than those living in urban regions (Stevens and Young 2010). The authors suggested that crowding in multi-family homes, low income levels, attendance at sports events and carnivals, and involvement in indigenous organizations were related to variations in gambling rates (Stevens and Young 2010).…”
Section: Introductionmentioning
confidence: 99%